2018
DOI: 10.1038/s41598-018-25277-z
|View full text |Cite
|
Sign up to set email alerts
|

Double domain polyethylenimine-based nanoparticles for integrin receptor mediated delivery of plasmid DNA

Abstract: The objective of the present study is to conjugate L-thyroxine PEI derivative onto another PEI to compensate the amine content of the whole structure which has been utilized for the ligand conjugation. Since αvβ3 integrin receptors are over-expressed on cancer cells and there is binding site for L-thyroxine on these receptors, PEI conjugation by L-thyroxine along with restoring the PEI amine content might be an efficient strategy for targeted delivery using polymeric nanoparticles. The results demonstrated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 50 publications
(92 reference statements)
3
27
2
Order By: Relevance
“…This could be the result of the coupling of two separate molecules of PEI via a linker, which increased the overall amine content of the PEI derivative. 21 This result is consistent with the buffering capacity measurement (vide supra). On the other hand, substitution of amines on PEI structure by different moieties has shown remarkable impact on its binding affinity.…”
Section: Binding Affinity Of Pei Derivative To Pdnasupporting
confidence: 83%
See 4 more Smart Citations
“…This could be the result of the coupling of two separate molecules of PEI via a linker, which increased the overall amine content of the PEI derivative. 21 This result is consistent with the buffering capacity measurement (vide supra). On the other hand, substitution of amines on PEI structure by different moieties has shown remarkable impact on its binding affinity.…”
Section: Binding Affinity Of Pei Derivative To Pdnasupporting
confidence: 83%
“…In our previous study on the conjugation of two HMW PEI molecules, the size increased to around 200 nm. 21 However, in this study no significant size increase was observed. This might be the effect of the conjugation of LMW PEI, which is a smaller molecule than HMW PEI.…”
Section: F I G U R Econtrasting
confidence: 68%
See 3 more Smart Citations